2021
DOI: 10.1186/s43046-021-00064-6
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of Dana Farber Consortium Protocol in newly diagnosed Egyptian adolescents and young adults with acute lymphoblastic leukemia: Tanta experience

Abstract: Background Intensive acute lymphoblastic leukemia (ALL) regimens in children improve the 5-year event-free survival (EFS) to reach ~ 90%. Adolescents and young adults (AYA) have EFS (30% to 45%). Young AYA ALL patients treated with pediatric chemotherapy protocols such as Dana Farber Consortium Protocol (DFCP) experience a better prognosis. This study aimed to assess the efficacy [EFS and overall survival (OS)] and the toxicity of DFCP in the treatment of Egyptian AYA with newly diagnosed ALL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
3
2
Order By: Relevance
“…In our study, no patients had chemotherapy drug-induced acute pancreatitis. This finding contradicts prior studies from other countries [11][12][13][14][15], which found acute pancreatitis despite its rarity. The differences between the present finding and the prior studies may be due to sampling size, the health status of patients, standard care of hospitals, the type of chemotherapy drug regimen, and short-term follow-up.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, no patients had chemotherapy drug-induced acute pancreatitis. This finding contradicts prior studies from other countries [11][12][13][14][15], which found acute pancreatitis despite its rarity. The differences between the present finding and the prior studies may be due to sampling size, the health status of patients, standard care of hospitals, the type of chemotherapy drug regimen, and short-term follow-up.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings indicated that children receiving chemotherapy drugs were more toxic and susceptible to pancreatitis than adults. The evidence is consistent with earlier findings [ 15 19 ]. Children's mean amylase and lipase enzyme levels increased as chemotherapy drug dosages increased from baseline to 4-week induction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mild drug-induced liver injury occurred in 5% of patients. The incidence of hepatotoxicity in this study is higher than in a prior studies in Egypt 21 and Singapore 18 but lower than in studies in the United States 19 and the Netherlands 20 for patients who received L-asparaginase as a chemotherapy induction. The difference could be attributed to the administration of four chemotherapy drugs in the current study, variations in hepatotoxicity grading criteria, the health status of patients, standard care of hospitals, and sample size.…”
Section: Discussioncontrasting
confidence: 72%
“…Hepatotoxicity occurred in 9.76% of patients treated with the Dana Farber Consortium Protocol (DFCP) in Egypt. Adolescents and young adults had favorable outcomes with DFCP but more toxicity 21 . Greater asparaginase activity levels resulted in statistically significant increases in ALT and bilirubin 22 .…”
Section: Introductionmentioning
confidence: 95%